The Impact of Bohemianism in Walt Whitman’s Poetry: A Critical Study of the Song of My Self - .Alsaeed, Norah H (كلية الإمارات للعلوم التربوية, 2022)
The objective of this paper is to explore the connection between Walt Whitman and Pfaff‘s members, and their influence on him and thence his compositions. It attempts to propound Whitman‘s attribution to Bohemianism in regard with his writings. The researcher aims to propose a critical study of "The Song of Myself", one of the prominent poems in the 12 poems collection published in Leaves of Grass, which is remarkable for its candid themes and expressions, that orients Bohemianistic attitude. The attempt also emphasizes on the simple style to celebrate the idea of sublimity evident in the poems. Notwithstanding, Walt Whitman was highly productive before the Civil War, in which he composed many distinguished poems. For several years before and after writing his poetry collection Leaves of Grass, the poet used to visit a secret bar called Pfaff. This bar is the center of the activities of the Bohemian movement in the middle of the nineteenth century. It was supported by many geniuses, poets, artists, musicians, and revolutionaries such as Henry Clapp. Pfaff witnessed many political and literary ideals; the Bohemians had two weekly publications Vanity Fair and New-York Saturday Press. In the light of such environment, Whitman found many supporters of his poetic vision, including competitors, critics, and close friends. Furthermore, his bohemian participations during his frequent visit to Pfaff won the acceptance of the American critic and poet Edmund Clarence Stedman, who was later identified as one of the makers of literary taste.
Keywords: ويتمان، والت، ت. 1892 م. -- القصائد الشعرية -- الأدب البوهيمي -- الشعر الغربي